System Analysis of Globalization Processes’ Axiological Evaluation on the Bolon Process Ethiology and Chronology - Kondur, Oksana; Katsero, Oksana; Trubchanina, Irina (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2020)
It is justified that the cross-border educational coordination activities have drawn public attention to the global challenges of the 21st century and have declared the necessity for sustainable development education to be at the forefront in the progress concept and strategies towards sustainability. Therefore, it is necessary to create a sustainable development specialists’ professional training system, especially, for the professionals with managerial and qualitative competences.